2015
DOI: 10.1371/journal.pntd.0003721
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism in Children Aged Three Years and Under: Relationship between Infection and Growth in Rural Coastal Kenya

Abstract: BackgroundParasitic infections, which are among the most common infections worldwide, disproportionately affect children; however, little is known about the impact of parasitic disease on growth in very early childhood. Our objective was to document the prevalence of parasitic infections and examine their association with growth during the first three years of life among children in coastal Kenya.Methodology/Principal FindingsChildren enrolled in a maternal-child cohort were tested for soil transmitted helmint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 17 publications
4
52
0
4
Order By: Relevance
“…Recent prospective data supports a greater focus on younger age groups at risk for GI parasitic infections. These prospective findings on children in Kenya indicated that STH infection by 2 years of age was associated with lower growth attainment in terms of length and head circumference relative to WHO standards [7]. Significant growth deficits, such as stunting, among children living in endemic areas commonly occur between 6 months and 2 years of age and overlap when STH infections become established [16].…”
Section: Preschool Age Childrenmentioning
confidence: 89%
See 3 more Smart Citations
“…Recent prospective data supports a greater focus on younger age groups at risk for GI parasitic infections. These prospective findings on children in Kenya indicated that STH infection by 2 years of age was associated with lower growth attainment in terms of length and head circumference relative to WHO standards [7]. Significant growth deficits, such as stunting, among children living in endemic areas commonly occur between 6 months and 2 years of age and overlap when STH infections become established [16].…”
Section: Preschool Age Childrenmentioning
confidence: 89%
“…Significant growth deficits, such as stunting, among children living in endemic areas commonly occur between 6 months and 2 years of age and overlap when STH infections become established [16]. Upon evaluating STH infections individually, infection with hookworm in 2 year olds was associated with below-average growth in length and head circumference; infection with Ascaris lumbricoides by 12 to 18 months was associated with decreased z-scores for all anthropometric indices at these ages [7]. Furthermore, infection with Strongyloides stercoralis by 30 months of age was associated with lower head circumference measures at this age [7].…”
Section: Preschool Age Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Серед 545 дітей віком до 3 років геогельмінтами було інфіковано 109 дітей (19 %), причому 7 % з них мали мультипаразитарну інфекцію. Зменшення антропометричних показників (маси тіла, довжини тіла, окружності голови) протягом перших 36 місяців життя було пов'язане поряд з іншими парази-тарними інфекціями з аскаридозом [7]. Паразитичне втручання іншого організму у процеси зростання дити-ни, «обкрадання», механічне пошкодження, алергізація, токсичне засмічення організму хазяїна не можна зали-шати без прицільної уваги, оскільки наслідки для макро-організму глобальні.…”
Section: вступunclassified